Hydatid Cyst of the Pancreas. An Experience with Six Cases - Shah, Omar Javed; Robbani, Irfan; Zargar, Showkat A; Yattoo, Ghulam N; Shah, Parveen; Ali, Sadaf; Javaid, Gul; Shah, Altaf; Khan, Bashir A (JOP. Journal of the Pancreas, 2010)
Context The pancreas is an infrequent site of hydatid disease. Objective This study aims at giving better insight into the diagnostic and managerial approach to the disease. Patients Six patients with hydatid cysts of the pancreas. Design Retrospective review of the clinical records. Results The six patients (four men, two women) ranged in age from 18 to 68 years. Five of the cysts were primary while one had an associated cyst in the liver. Abdominal pain, vomiting, abdominal mass and dyspeptic symptoms were seen in cysts involving the body and tail. Two patients having cysts in the head of the pancreas presented with obstructive jaundice. An indirect hemagglutination test and an enzyme-linked immunoabsorbent assay were positive for the presence of specific hydatid antibodies in four patients. Abdominal ultrasonography, computed tomography and magnetic resonance cholangiopancreatography (MRCP) successfully imaged the cysts and also defined the relationship of the lesion with the pancreatic duct. All patients underwent surgical exploration. Three patients had intraoperative fine needle aspiration cytology of the cystic lesion for microscopic and electrolyte analysis. A preoperative diagnosis was possible in two patients and, in the other four, the diagnosis was made intraoperatively and confirmed on histopathological examination. Patients with cysts located in the tail underwent a distal pancreatectomy with a splenectomy while those with cysts in the body had a pericystectomy or central pancreatectomy. Cysts of the head were treated with evacuation, partial cystectomy and tube drainage. There were no postoperative complications, and no evidence of cyst recurrence was observed during the follow-up period. All the patients were followed up at three-month intervals with a mean follow-up time of 58.7 months (rang: 4-120 months); no patient had cyst recurrence or dissemination. Conclusion A hydatid cyst is an uncommon cause of cystic lesions in the pancreas and should be included in the differential diagnosis of cystic lesions of the pancreas, especially in endemic areas. Intraoperative fine needle aspirate for microscopic and electrolyte estimation seems to be an effective method for establishing a proper diagnosis. MRCP, which can depict the communication of the cystic lesion with the pancreatic duct, helps in defining the type of surgical treatment. Cysts in body and tail are best treated by resectional methods whereas, for those in the head region, a cystectomy with simple drainage is a simple, quick and effective solution. Image: Extraction of a germinating membrane from a hydatid cyst in the pancreatic head.